Dependency Traits, Relationship Power, and Health Risks in Women Receiving Sexually-Transmitted Infection Clinic Services. Issue 3 (3rd July 2017) - Benotsch, Eric G.; Sawyer, Ashlee N.; Martin, Aaron M.; Allen, Elizabeth S.; Nettles, Christopher D.; Richardson, Doug; Rietmeijer, Cornelis A.
ABSTRACT: In prior research, having traits consistent with a personality disorder has been shown to be related to substance use and high-risk sexual activity; however, few studies have examined relationships between dependency traits and health-jeopardizing behaviors. Individuals with traits consistent with dependent personality disorder may be more likely to be in a primary relationship characterized by unhealthy conditions, including physical abuse from a partner, low assertiveness in sexual situations, and partner infidelity. In addition, dependency traits may be associated with unhealthy coping (e.g., through substance use). To examine associations between dependent personality traits and these types of health-related behaviors, 198 women seeking sexually transmitted infection clinic services completed a computer-assisted assessment of dependent personality traits, substance use, unhealthy conditions in primary relationships, perceived sexual and relationship power, and sexual risk related to condom use. Dependency trait scores were correlated with the use of cocaine, heroin, and methamphetamine. Participants high in dependency traits reported low perceived power within their relationships and less say in sexual behaviors, including condom use. In a series of multivariate analyses, dependency traits significantly predicted having been hit by a partner, staying with a partner after he cheated, having sex because of threats, and fear of asking a partner to use a condom. Dependency traits were also associated with lower past condom use and lower future condom use intentions. Results suggest that dependent personality traits may place women at higher risk for physical abuse and harmful health behaviors.